Li[LiCs2Cl][Ga3S6]: A Nanoporous Framework of GaS4 Tetrahedra with Excellent Nonlinear Optical Performance - Liu, Bin‐Wen; Jiang, Xiao‐Ming; Li, Bing‐Xuan; Zeng, Hui‐Yi; Guo, Guo‐Cong (Angewandte Chemie International Edition, 2020)
A large nonlinear optical (NLO) coefficient and a wide band gap are two crucial but contradictory parameters that are difficult to achieve simultaneously in a single infrared (IR) NLO compound. A salt‐inclusion chalcogenide (SIC), Li[LiCs2Cl][Ga3S6] (1), was prepared that presents a nanosized tunnel framework constructed from monotype chalcogenide tetrahedra. Highly oriented covalent GaS4 tetrahedra in the host lead to a moderate second harmonic generation response (0.7 AgGaS2), and ionic guests effectively broaden the band gap to the widest value (4.18 eV) among all IR NLO chalcogenides, thereby achieving a remarkable balance between NLO efficiency and band gap. The salt‐inclusion chalcogenide Li[LiCs2Cl][Ga3S6] is presented, which features a 3D framework composed of [Ga3S6] nanosized tunnels. Introduction of an ionic guest to the covalent chalcogenide host produces a material with a moderate nonlinear optical (NLO) coefficient and an ultrawide band gap (Eg). These characteristics are promising for the development of infrared (IR) NLO materials.